DYSTOCIA IN A DOE DUE TO HYDROCEPHALOUS FETUS - REDDY, C VENKATESWAR; REDDY, Y. V. PRIDHVI DHAR; JYOTHI, K (The Indian Journal of Animal Reproduction, 2022)
Doe with 4 years age was presented to the college clinic with a history of severe straining past two days.Pervaginal examination revealed that cervix was not dilated and was treated with 10mg of Valethamate bromide and no improvement was noticed. Hence, caesarean section was performed to relieve the foetus.After caesarean operation, ahydrocephalus fetus was delivered. The foetus was malformed with an enlarged head. Post mortem examination revealed an abnormal increase in the amount of cerebrospinal fluid within the cranial cavity accompanied by expansion of cerebral ventricles, enlargement of the skull especially forehead and atrophy of brain.The Present case discusses report about the rare condition in doe with dystocia due to hydrocephalus fetus.